Planting seeds of technology [business start-up management]. - Perry, T.S.
In this paper, the author describes how, after successfully cofounding three communications companies, Judy Estrin is going for a fourth, this time to beget not more products, but more companies
Keywords: Judy Estrin; Business start-up management; Communications companies; Corporate takeover